Left‐sided colitis and extensive colitis have similar colectomy rates after index episode of acute severe colitis: A long‐term follow‐up study - Jain, Saransh (JGH Open, 2017)
BACKGROUND AND AIM: The extent of disease of ulcerative colitis (UC) has been found to be a predictor of acute severe colitis (ASC), but it is unclear whether the extent of disease at the index episode of ASC is a predictor of long‐term outcome. METHODS: Hospitalized patients satisfying Truelove and Witts’ criteria under follow‐up at a single center from January 2003 to December 2016 were included. The extent of disease at index ASC was classified according to the Montreal classification as left‐sided or extensive colitis. Extent was used to predict the long‐term risk of colectomy or steroid dependence following an index episode of ASC. RESULTS: Of 2076 patients with ulcerative colitis, 241 (12%) had an index episode of ASC. In total, 34 (14%) patients underwent a colectomy at index admission and 53 (26%) over a median follow‐up of 48(1–172) months. Left‐sided colitis and extensive colitis did not differ in the rate of colectomy at index admission (12% vs 15%, P = 0.4) and colectomy in follow‐up (31% vs 23%, P = 0.17). Readmission due to ASC was also similar between the two groups (28% vs 32%, P = 0.6). CONCLUSION: Extent of disease at index ASC does not predict colectomy at admission and over the long term.